Tumpang Tindih (Overlapping) Kewenangan Komisi Pengawas Persaingan Usaha (KPPU) dan Badan Pemeriksa Keuangan (BPK) dalam Pengawasan Pengadaan Barang dan Jasa Pemerintah - Simanjuntak, Predderics Hockop; Novta Rizky Askohar Putri; Josephat Mario Seran Tahuk; Andi Muh Teguh Hakim (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
Government procurement of goods and services plays a crucial role in national development, yet it is highly susceptible to collusion and financial mismanagement. In this context, the Business Competition Supervisory Commission (KPPU) and the Audit Board of Indonesia (BPK) serve as key supervisory bodies. KPPU focuses on preventing unfair business practices such as tender collusion, while BPK emphasizes the efficiency and accountability of state finances. This study aims to analyze the overlapping authority between these two institutions and explore solutions for harmonizing their roles. Using a normative juridical method with a descriptive-analytical approach, the findings reveal overlapping areas of supervision that risk undermining effectiveness and creating legal uncertainty. Therefore, a clear regulatory framework—through new legislation or revisions to existing presidential regulations is essential to ensure a coordinated, fair, and efficient oversight system.